COMMUNITY STRUCTURE OF ECHINODERMS IN THE COASTAL WATERS OF SUNGAI NIPAH PESISIR SELATAN REGENCY - Meitasuri, Gevi; Efriyeldi, Efriyeldi; Nasution, Syafruddin (Asian Journal of Aquatic Sciences, 2023)
Echinoderms are thorn-skinned invertebrates such as sea stars, snake stars, sea urchins, sea cucumbers, and sea lilies. Echinoderms are marine animals that act as cleaners for the marine environment, especially the coastal environment. This research was conducted in September 2021 in the coastal waters of Sungai Nipah, Pesisir Selatan Regency, West Sumatra Province. The purpose of this study was to determine the structure of the echinoderm community which includes species, abundance, relative abundance, diversity, uniformity, dominance, and distribution patterns. The method used in this research was a survey method, to determine the observation station using a purposive sampling technique. Based on the research results, the species of echinoderms found in the coastal waters of Sungai Nipah Village are Holothuria scabra, H.atra, and Ophiocoma scolopendrina. The abundance of echinoderms obtained ranged from 7,407–11,481 ind/ha. Echinodemata diversity has an average of 1.13 which belongs to the medium category. The uniformity of echinoderms has an average of 0.13 which is included in the category of very low species uniformity. The average value of dominance is 0.51 which means that there are species that dominate in these waters. The distribution pattern of echinoderms in the coastal waters of Sungai Nipah is uniform.